The trade openness–gender wage differential nexus: Household‐level evidence from Ghana. Issue 1 (11th January 2022) - Orkoh, Emmanuel; Blaauw, Derick; Claassen, Carike
Abstract: The literature on trade openness–gender wage differential nexus in developing countries has revealed heterogeneous findings that reflect the opposing theoretical perspectives and the need for more country‐specific analyses that will allow for proper policy targeting and implementation. This paper contributes to the growing literature on this issue from a Ghanaian perspective using disaggregated household data. The Oaxaca decomposition estimates show a wage gap of approximately 21% and evidence of the endogenous growth theory that trade openness widens the gender wage gap particularly among urban and low‐skilled workers. The Ministry of Trade and Industry must collaborate with the Ministry of Employment and Labour Relations to review the existing labor and investment policies to improve the wages and other working conditions of women engaged in trade‐oriented economic activities, including the nontraditional export that has experienced higher integration into global trade in recent years.